Soberania e princípios do processo penal em face do tribunal penal internacional - Araújo, Maurício de Carvalho (2005)
The objective of this paper is to assess the constitutional bases that allowed Brazil to subscribe to the International Criminal Court and the resulting obligation to respect its jurisdiction and to provide judicial cooperation. Therefore this paper discusses the concept of State sovereignty, within the context of national and international law and its historical evolution, from the beginning of international law and the sovereign States up until the institutionalization of an international legal order with the enforcement of an international jus cogens, based on the pacific resolution of conflicts and on the universalization of human rights. The creation of the International Criminal Court is discussed from the principles of complementarity and non-intervention. This study analyses the compatibility between the International Criminal Court and the current concept of sovereignty, the system of the United States Organization, the treaties on human rights and the constitutional principles of criminal proceedings present in the Brazilian Constitution of 1988. In order to evaluate the compatibility among these systems, it was necessary to establish a comparison between the principles of criminal proceedings in the Federal Constitution of 1988, especially the due process of law and the principle of a fair trial, present in international treaties on human rights and in the international military courts of Nuremberg and Tokyo, in the ad hoc courts of the United Nations for the former Yugoslavia and Rwanda and in the International Criminal Court from the Statute of Rome. Finally, this paper analyses the principles of criminal proceedings in the International Criminal Court, as in the wording of the Statute of Rome, comparing them with the principles of a fair trial as determined by international treaties on human rights, which are a true international jus cogens.